The effect of technology on copyright - Gachago, Mwangi (Centre for Law and Society, 2026)
Copyright and technology have a long and intertwined history during which both have felt their influence on each other. The exclusive rights of reproduction and distribution given to the creators of artistic and literary works today to are very different from what they were 500 years ago when this relationship began. Copyright developed as a direct consequence of the invention of the printing press. Before its invention, the principle protecting author's rights did not exist because the mass reproduction of literary works was not possible. Gutenberg's invention of movable type, however, revolutionised the industry and the stationers in England moved from reproducing single volumes by hand to producing many more copies to match the growing demand resulting in books gaining significant financial value. Value that was difficult to access by the authors of the books until 200 years later when the Statute of Anne, in an effort to encourage the sustained production or original works, granted the authors exclusive rights to their works and started the whole copyright story. Modern national copyright legislation has evolved with different influences throughout history. However, as the world continued to develop and cross border activity flourished national copyright legislation was not sufficient to govern what had become a global concern. International agreements were developed over time that reacted to technologies influence on copyright while at the same time setting the baseline for national copyright legislation to grow around. The Berne Convention remains the most important international agreement on copyright and most national laws and international instruments have developed with reference to it. Following the age of the printing press, the next major technologies to influence copyright were the new recording and broadcast technologies bringing with them, revolutions that forced major shifts in copyright legislation in its efforts to curb infringement. The current digital era poses the biggest challenge copyright legislation has had to face in its history with technology enabling copyright infringements of a scale by far exceeding all other periods combined. A lot of laws and litigation have marked the path leading up to the situation today with many remedies proving ineffective in reversing the scale of copyright infringement. It is time that the copyright industry stopped fighting new technology and realise that their survival might depend on finding new business models that incorporate technologies like P2P networks into their strategies.